Ryzyko w transakcjach leasingowych - Warelis, Alina (Risk in Leasing Transactions, 2005)
Following market economy development in Poland new fields of research on risk as well as risk management of economic undertakings (in this study leasing transactions) appeared. The decision to choose leasing as a form of financing an investment is based upon a forecast of conditions of future unit's activities, containing incertitude. Whereas expected effects contain risk in regard to financing with the use of leasing. Problems, in case of leasing transactions, seem to concern both field of leasing risk evaluating and selection of evaluation method that include investment risk. In this study risk of leasing transactions was estimated on the side of leaseholders as well as leasing companies. Risk analysis of defined kinds of risk, important from the leasing agreements point of view, was made. Descriptive techniques and list of control questions method were used in the research. In the summary it was stated that leasing transactions risk constitutes a problem that should be analyzed from the unit's planning an undertaking point of view that would include detailed conditions of its leasing agreement. Whereas methods used in risk evaluating and field of its possible appearance depend on decisions of people who evaluate the risk of an undertaking.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 362-371